Impact of digital modules on math achievement by gender and locality - Kapoor, Jyoti; Cheema, Guneet Kaur (Journal of Interdisciplinary Studies in Education, 2024)
Digital modules typically refer to self-contained units of online learning materials designed for specific topics or learning objectives. The researcher developed digital modules for three specific math units and conducted a three-week experiment in six schools in three districts of Punjab. The purpose of the study was to find the effectiveness of digital modules. The study revealed a statistically significant difference in gain achievement scores and posttest achievement between the experimental and control groups. The t statistic for gain achievement scores was 2.41, indicating a p-value of 0.016, and 2.70 for posttest achievement. This suggests a significant difference in learning outcomes between the two groups.